Let Jamie's test score equal x and Paul's test score equal y. The problem states that the total of their test scores combined equals 143. That is, x + y = 143
Since this equation has two unknown variable, we need to substitute one of the variables with an expression that is in terms of the other variable. The problem states that Jamie earned 15 more points on her test than Paul earned on his, which brings us to
the following:
Paul's test score = y
Jamie's test score = x ==> x = y + 15
With this,
x + y = 143
(y + 15) + y = 143
y + 15 + y = 143
2y + 15 = 143
2y + 15  15 = 143  15
2y = 128
2y/2 = 128/2
y = 64
Therefore,
Paul's test score = y = 64
Jamie's test score = x = y + 15 = 64 + 15 = 79
4/2/2013

Tamara J.